Estudio para evaluar una oportunidad de autogeneración eléctrica mediante el establecimiento de centrales hidroeléctricas en PINDECO Pacífico - Jiménez Zúñiga, Adrián (Instituto Tecnológico de Costa Rica, 2013)
Today, the world’s overpopulation problems as well as the growing demands of modern societies for amenities are creating a rising consumption of electricity. As a consequence, there is a need to use less renewable sources such as hydrocarbons which in turn affects tropical countries with an abundance of water like Costa Rica. In the dry season, plenty of water resource is essential for the irrigation of pineapple in places like Buenos Aires and Pérez Zeledón. For that matter, concessions have been made to use water from surrounding basins according to their volume of water. Some of these concessions are only used 85% during the rainy season (9 months). Therefore, the objective of this study is to showcase an alternative of electric selfgeneration for PINDECO’s hydroelectric centrals in the Pacific through a planned establishment according to PMBOK methodology (PMI, 2008).Thus, there would be a better flow and uptake of already existing water in PINDECO’s farms. To achieve the aforementioned, it is necessary to analyze the feasibility of PINDECO’s hydroelectric centrals in the pacific in order to determine how profitable the project is. Secondly, it is important to decide on the components and implementation procedures according to the “PMBOK guide” (PMI, 2008) in its fine areas of knowledge. Despite the fact that a descriptive study was mostly carried out to solve specific needs of the investigative process, it was also necessary to do a correlational study of some sections. As a result of the feasibility study, it was determined that the project is viable from the technical, legal-environmental, organizational and financial point of view. Hence, the image of Fresh Del Monte Produce Inc. is consolidated as a company committed to reducing the carbon footprint. Similarly, the plan proposed meets a series of support processes which become a succinct and innovative guide for the establishment of PINDECO’s hydroelectric centrals in the Pacific. After having ended the study, it is recommended that a more detailed technical analysis be made so that other power-generating places not covered by the investigation within Del Monte farms can be established.
Proyecto de Graduación (Maestría en Gerencia de Proyectos con Énfasis en Proyectos Empresariales). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2012
Keywords: Administración; Gestión de proyectos; Planificación de proyectos; Estudio de factibilidad; Proyectos hidroeléctricos